Immunization with Salmonella Abortusequi phage lysate protects guinea pig against the virulent challenge of SAE-742. (November 2018) - Abhishek,; Kumar, B.; Anjay,; Mishra, A.K.; Prakash, C.; Priyadarshini, A.; Rawat, M.
Abstract: Salmonella Abortusequi causes important clinical diseases in horses possibly leading to abortion. In the present investigation, the protective efficacy of both plain and aluminum hydroxide gel adjuvanted phage lysate was evaluated in guinea pig model. Broad host range bacteriophage PIZ -SAE-2, was characterized and used for generation of lysates. Three different lysate batches, produced through separate cycles and characterized, were pooled together for immunization study. Plain and adjuvanted phage lysate preparations elicited both humoral and cellmediated immunity. The adjuvanted lysate at a dose of 50 μl elicited the highest protective efficacy against direct challenge at 28th DPI. Thus, the present study describes a new method of bacterial inactivation for producing a new class of better & safe immunprophylactic agents. This is the first report of producing an inactivated vaccine candidate using a new approach against equine salmonellosis.